The Influence of Profitability, Liquidity, Leverage and Growth on Economic Profitability of PT. Indika Energy, Tbk Year 2016–2021 - Situmorang, Humala; Lumbantoruan, Rutman (Fundamental Management Journal, 2022)
This study aims to determine the factors that cause the company's ability to earn profits as measured by economic profitability as the dependent variable in obtaining profits as measured by economic profitability as the level of liquidity, leverage, and the level of company activity as independent variables are these factors.Data is collected based on financial report data from 2016 to 2021 (quarter 3), and using multiple regression analysis.The research' findings reveal that the company's liquidity, leverage, and amount of activity have only a little impact on its economic performance. Simultaneously, liquidity, leverage, or activity level have no impact on a company's economic performance. While the coefficient of determination is 2.5 percent, it shows the extent of the effect of liquidity, leverage, and the amount of corporate activity in determining the economic profitability of PT Indika Energy, Tbk.Keywords : Liquidity, leverage, activity level and company's economic profitability.